2001
DOI: 10.1046/j.1365-2664.2001.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use and diet of skylarks Alauda arvensis wintering on lowland farmland in southern Britain

Abstract: Summary 1.The habitat use and diet of skylarks wintering on lowland farms were studied to assess whether changes in agricultural practice could have reduced their most favoured wintering habitats or foods. Faecal samples were collected and soil seed densities were estimated. Skylarks in 122 cereal stubble fields in Oxfordshire were counted monthly to examine habitat use. 2. Cereal stubble fields were more likely to be occupied than other crops, and densities of birds in occupied fields were high. Barley stubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 26 publications
(48 reference statements)
2
60
1
1
Order By: Relevance
“…In this study, cereal crops were used in proportion to availability and previous studies have ranged from reporting limited selection (Donald et al 2001) to avoidance (Wilson et al 1996, Buckingham et al 1999, Robinson & Sutherland 1999. Contrary to Wilson et al (1996), this study found positive selection of oilseed rape crops and stubbles and root crop stubbles.…”
Section: Habitat Selection -Patch Scalecontrasting
confidence: 44%
See 4 more Smart Citations
“…In this study, cereal crops were used in proportion to availability and previous studies have ranged from reporting limited selection (Donald et al 2001) to avoidance (Wilson et al 1996, Buckingham et al 1999, Robinson & Sutherland 1999. Contrary to Wilson et al (1996), this study found positive selection of oilseed rape crops and stubbles and root crop stubbles.…”
Section: Habitat Selection -Patch Scalecontrasting
confidence: 44%
“…Cereal stubble fields, especially those with abundant weeds, were the most positively selected farmland habitat type as found by Wilson et al (1996), Chaney et al (1997), Wakeham-Dawson & Aebischer (1998), Buckingham et al (1999), Robinson & Sutherland (1999), and Donald et al (2001). No difference was found between barley and wheat stubbles despite the fact that barley stubbles support greater cover of crop volunteers and broadleaved weeds (Robinson & Norris 2001).…”
Section: Habitat Selection -Patch Scalementioning
confidence: 70%
See 3 more Smart Citations